Structural Characterization for Carbon Nanotubes Treated with Concentrated Nitric Acid - Ji, Bao-Hua (Asian Journal of Chemistry, 2012)
In order to improve the compatibility between multi-walled carbon nanotubes and polymer chains and obtain well-dispersed composite polymers. Multi-walled carbon nanotubes were modified by concentrated nitric acid and the effect of concentrated nitric acid on the chemical structural changes of multi-walled carbon nanotubes was investigated by means of FT-IR spectrometer, Raman spectra, thermogravimetric analysis and scanning electron microscope. It was demonstrated that the acidized treatment can not only remove impurities inside carbon nanotubes, but also bring in the carboxyl groups into the surface of carbon nanotubes while not destroying the integral structure.